Health-related quality of life in patients with relapsing-remitting multiple sclerosis treated with subcutaneous interferon β-1a in Iran. (3rd June 2017) - Pakdaman, Hossein; Amini Harandi, Ali; Gharagozli, Koroush; Abbasi, Mehdi; Tabassi, Abdolreza; Ashrafi, Farzad; Ghaffarpor, Majid; Sharifi, Shahdak; Delavar Kasmae, Hosein; Assarzadegan, Farhad; Arabahmadi, Mehran; Behnam, Behdad
Abstract : Purpose : Multiple sclerosis (MS) requires long-term therapy and can affect many aspects of a patient's life, including quality of life. MS patients score lower on health-related quality of life (HRQoL) measures. The efficacy of subcutaneous interferon (IFN) β-1a has been extensively evaluated by using objective measures but its impact on HRQoL is currently unclear. In this observational study, we evaluated HRQoL of Iranian patients with relapsing-remitting MS (RRMS) treated with IFN β-1a by using short-form 36 (SF-36) and multiple sclerosis international quality of life (MusiQoL) questionnaires. Methods : Four hundred recruited RRMS patients were treated with human serum album free IFN β-1a for 1 year. Patients were required to fill in SF-36 and MusiQoL questionnaires at the first visit and at each follow-up visit. Expanded disability status scale (EDSS) evaluation was performed at baseline and at each visit. Comparisons in HRQoL between visits were calculated using Cohen's d effect size. The relationship between change in EDSS score and the score of each questionnaire was calculated using Pearson correlation coefficients. Results : Three-hundred and eighty three completed the study. Two-hundred and thirty nine were female. Mean (SD) age was 28.75 (±5.49). After 1 year, overall MusiQoL Index score effect size was −0.16 and SF-36 physical component and mental component showed overall effect sizes of −0.28 and −0.53, respectively. Mean (range) EDSS change was 1 (1–4). Three-hundred and seventy four were clinically stable with mean (range) EDSS change of 0.1 (−2–0.5). Increase in EDSS was linked to a decrease in both MusiQoL and SF-36. Conclusion : We found that, HRQoL did not change significantly over the first year of therapy. Furthermore, decreases in HRQoL were inversely correlated with increases in EDSS score.